Student's Perspective On Face-To-Face Learning UMS Academic Year 2021/2022 In Applying Health Protocol - Fitriani, Nurlaila; Sejati, Ilham Kukuh; Widya Utami, Pramudita Setya; Izzah, Risdiana Nur; Putri, Naura Farkhia; Safitri, Aura (Jurnal Ilmu Kesehatan, 2022)
In the 2021/2022 academic year when the Covid-19 pandemic is still ongoing, various educational institutions have begun to carry out face-to-face learning. The implementation of face-to-face learning in every educational institution cannot be separated from the application of strict health protocols to prevent the transmission of Covid-19. One of the educational institutions that will implement face-to-face learning is the Muhammadiyah University of Surakarta. This study aims to look at the perspective of students as learning actors in the application of health protocols and the effectiveness of learning at the Muhammadiyah University of Surakarta when face-to-face learning is applied. The survey method used in this study and followed by one hundred respondents consisting of universities of health sciences participated by filling in the given. Aspects assessed in this study are learning effectiveness, lecturer competence, and infrastructure which are divided into thirteen statements in which respondents can answer using a Likert scale format. The data obtained were processed using descriptive quantitative analysis method of percentage technique. Based on data analysis, the majority of respondents have positive opinions regarding the preparation of face-to-face learning by universities in implementing health protocols. However, because the research is subjective and limited to health science students, further research needs to be done.